Descriptive analysis of staff satisfaction and turnover intention in a Malaysian University - Mohamad Hazeem, Mohmad Sidik; Ab Hamid, Mohd Rashid; Abdullah, Ibrahim (AIP Publishing, 2017)
This paper discussed the descriptive analysis of staff satisfaction in education organisation. This study employed a cross-sectional study involving a total of 1042 of respondents from a university in east coast of Malaysia. The survey covers six dimensions of staff satisfaction which are leadership, staff involvement, workload, self-development, working environment and communication. From the analysis of the mean score, it reveals that the staff enjoyed moderate level of satisfaction and the findings of the study generally support the past findings in the literature. This study paved the way for in-depth investigation towards staff satisfaction at the university under study.